Synergistic effect of hydroxyapatite-magnetite nanocomposites in magnetic hyperthermia for bone cancer treatment - Anwar Aneela; Sadiqa Ayesha; Intisar Azeem; Rashid Amin Ur; Razaq Tabassam; Aldossari Samar A.; Mushab Mohammed Sheikh Saleh; Park Dong Yong; Choi Dongwhi (Nanotechnology Reviews, 2024)
Hydroxyapatite/magnetite (HA-Fe3O4) nanocomposite materials that have the synergistic ability to produce heat when in direct bonding with a bone through HA are regarded competent hyperthermia therapies of bone carcinoma treatment. HA-Fe3O4 nanocomposites with various magnetite concentrations (10, 20, and 30 wt%) were quickly synthesized using a novel continuous microwave-assisted flow synthesis (CMFS) process in a 5 min residence duration at the conditions of pH 11. In this process, initially, phase pure hydroxyapatite and superparamagnetic magnetite nanoparticles followed by a series of HA-Fe3O4 nanocomposites were formed, without a subsequent aging step. The obtained nano-product was physically analyzed using Brunauer-Emmett-Teller (BET) surface area analysis, transmission electron microscopy, and X-ray powder diffraction analysis. X-ray photoelectron spectroscopy was used for the chemical structure analysis of the final nanocomposite product. Zeta potential measurements were carried out to determine colloidal stability associated with the surface charge of the nanocomposites. The magnetic properties were determined using a vibrating sample magnetometer. The results indicated the high magnetization property of the obtained nanoproduct, suitable for hyperthermia application. HA-Fe3O4 nanocomposites have shown remarkable antimicrobial properties against E. coli and S. cerevisiae. Thus, the CMFS system facilitated the rapid production of HA-Fe3O4 nanocomposite particles with fine particle size.